Pengaruh Penerimaan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) dan Bea Perolehan Hak atas Tanah dan Bangunan (BPHTB) terhadap Penerimaan Pajak Daerah di Kota Bandung - Tasha Nurafifah; Arry Irawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
Local tax revenue in Bandung are still not maximal due to some contraints, especially for land and building tax if rural and urban sectors and also land and building title transfer tax. Therefore, BPPD is trying to solve problem by implementing several policies that make it easier for taxpayers to pay taxes. The purpose o this study was to find out the effect of the land and building tax o rural and urban sectors and land and building title transfer tax revenue to local tax revenue in Bandung in 2015-2019, both partially and simultaneously. The research method used in this study is a quantitative method with a descriptive approach. The type o data used is quantitative data, documentary data, and subject data. The sample is this study was 60 months from January 2015 to December 2019. The data analysis method used is multiple regression analysis. The result of this study shows that the land and building tax of rural and urban sectors and land and building transfer tax revenue have a significant and positive effect both partially and simultaneously on local tax revenue in Bandung City.